How COVID-19 Pandemics Influences Chinese Economic Sustainability - Maksim Vasiev; Kexin Bi; Artem Denisov; Vladimir Bocharnikov (Foresight and STI Governance)
China was the first country to face the COVID-19 outbreak. Owing to the prompt and decisive actions of the authorities, and the consolidation of society, the country has overcome the peak of incidence, and economic activity is gradually recovering. The paper shows how COVID-19 affects the key industries and simulates the impact on supply and transportation channel work. Using the input-output spatial data, migration index indicators, and pandemic spread statistics, we simulate different scenarios for changes in China provinces’ production and consumption under the post-coronavirus epidemic situation. Calculations were made for 31 provinces and 42 sectors of the Chinese economy. We got a model that coronavirus outbreak disaster influences on carbon dioxide emission, level of hazardous wastes and Energy-Resource Efficiency Rating. Basing on financial and migration flows between China provinces, we chose the most effective after-coronavirus outbreak model. Our main recommendation is that one needn’t to carry out any segregation of consumers. It is necessary to distribute the damage as evenly as possible between all provinces equally. We believe that such an approach will allow the Chinese economy to suffer the least damage and recover faster. Finally, we analyze the development of the post-epidemic financial flows from China to Russia, with the horizon until 2025. In all scenarios, the temporary decline of the bi-directional is expected. The results of the study may be useful for other countries in developing policies to overcome the post-epidemic crisis.